(untitled) (Research, Society and Development, 2022)
The use of herbal medicines for weight loss has a great trajectory in the history of Brazil, but currently there are not many studies that prove its safety and efficacy. As a general objective, this research evaluates the risks and benefits of the use of herbal medicines and slimming drugs, among them Hibiscus rosa-sinensis L. This study is justified by the need for more studies to prove the efficacy of hibiscus as a herbal medicine, given its popular and even traditional use, used for weight loss. This is an experimental, cross-sectional, descriptive, and correlational study conducted between people living in São Paulo and regions, virtually applying a questionnaire through Google Forms to survey the use of herbal medicines to lose weight. Obtaining their results through the statistics collected from a group of 145 people, aged between 20 and 40 years, supported by bibliographic research searched in the databases: Scholar Google, Lilacs, Scielo.